Spatial metaphors and political practices - Chandhoke, Neera (New Delhi, 1991)
Linguistic analysis has sensitized us to the notion of language being double coded. Metaphor in this can mean a straightforth representation of phenomena, i.e. the creation of an image expressing some established rules of discourse or practice. For instance: the sense handmill is the signifier of feudalism; just as the factory chimney and inner cities are the representative codes of Industrial Capitalism and the telecommunications tower is that of advanced capitalism. Alternatively, metaphor acquires historical significance in a changing field of discourse. It indicates the struggle of the 'new' against the established foms. It is in this sense a language which communicates by expansion and subversion of the accepted rules. It may represent a break, a merger, a recombination, or all three. Therefore, metaphor not only connotes the new born out of the old, it interrogates the old; reveals the contradictions and examines the spaces within the old. It thus signifies both new possibilities and the loss of possibilities.
Keywords: Political science